Development of E-Worksheet based Liveworksheets with STEM-5E Approach to Improve Science Process Skills Students Class VIII on Vibration and Wave Material - Azfi, Annisa Sholihah; Setiawan*, Agung Mulyo; Affriyenni, Yessi (Jurnal Pendidikan Sains Indonesia, 2025)
Science learning should offer students meaningful learning experiences to develop their skills. In facing the era of globalization, 21st century skills are an important aspect that students must have. This research aims to develop e-worksheet based on liveworksheets with STEM-5E approach to improve science process skills on vibration and wave material that valid to be used by the aspect of validity, practically, and effectiveness. This type of research is research and development using the 4D model (define, design, development, disseminate). The research design used was quasi-experimental, namely select control group and select experimental group. The two classes used were class VIII B as control class with 30 people and VIII A as experimental class with 31 people. The research location was carried out at Junior High School 01 Karangploso. Data collection techniques were obtained using research instruments including validation sheets, response questionnaire sheets, pretest-posttest questions, and e-worksheet observation sheet. The validity results obtained a validity of 92.88%, with very valid criteria. This validity was carried out on the aspect of material, media, STEM-5E and SPS which received value of 87.41%, 91.25% and 100%. Practicality results in terms of students and teacher response questionnaires received value of 87.64% and 88.16% with very practical criteria. Effectiveness result in the terms of e-worksheet observation sheets received value of 96.78% and the N-Gain score (%) of the experimental class which got value of 66.76% in the quite effective category and the control class was 45.53% in the less effective category. Therefore, it can be concluded that this e-worksheet is valid, practical, and effective used to improve science process skills in class VIII vibration and wave material